UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI PENDEKATAN TaRL PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV DI MIS BIDAYATUL HIDAYAH 3 MEDAN - Ratna Dewi; Dinda Yarshal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This Classroom Action Research aims to improve students' critical thinking skills in Pancasila Education learning through the application of the TaRL approach to class IV students of MIS Bidayatul Hidayah 3 Medan. This research was conducted at MIS Bidayatul Hidayah 3 Medan. The subjects of this study were class IV-A students with a total of 20 students. This research was conducted in May 2025-June 2025, even semester of the 2024/2025 academic year. This classroom action research was carried out using the research cycle model from Kemmis and Mc. Taggart. This research was conducted through four stages, namely action planning, action implementation, observation/evaluation and reflection as a basis for re-planning for further research. In cycle I, students' critical thinking skills in Pancasila Education learning who got a score of ≥70 were 15 students or a percentage of 75%. In this second cycle, there has been an increase in the results of critical thinking skills in Pancasila Education learning which received a score of ≥70 for 17 students or a percentage of 85%. The percentage of teacher action monitoring instruments in cycle I meeting 1 was 55%, meeting 2 was 63.3%, meeting 3 was 73.3% and student action monitoring instruments in cycle I meeting 1 were 47.5%, meeting 2 was 60%, meeting 3 was 72.5%. The percentage of teacher action monitoring instruments in cycle II meeting 1 was 75%, meeting 2 was 83.3%, meeting 3 was 95% and student action monitoring instruments in cycle II meeting 1 was 75%, meeting 2 was 85%, meeting 3 was 95%. The implication of this classroom action research is that the critical thinking skills of grade IV MIS students in Pancasila Education learning can be increased by implementing the TaRL approach in the learning process.